Cronologia Kona Ba Timor Loro Sa'e Edisaun 4 - Timor Loro Sa'e-Nippon Culture Center (Dili : Timor Loro Sa'e-Nippon Culture Center, 2005)
This chronology of Timor Loro sa'e was written by TNCC in English at first, and then translated it into Tetun by individuals.
Edisaun statement treated as part numbering.
Text in Tetum (Tetun)
Keywords: Timor-Leste -- History -- Chronology -- 20th century; Timor-Leste -- History -- Chronology -- 21th century